Psicoeducação alimentar e nutricional em mulheres com obesidade: uma proposta sistêmica - Otto, Ana Flávia Nascimento (2022)
This thesis proposes a model of food and nutrition education to change eating behavior in obesity in adults, based on Bowen's Systemic Family Therapy. It argues that an intervention tcv change the eating behavior of adults with obesity should seek both to improve the quality of food and to favor a process of self differentiation, in order to promote emotional self-regulation and greater control over food choices. From the understanding of food choice as a complex issue and as part of human development in Bowen's perspective, a form of group intervention was built: the Group and Systemic Health Promotion - GPSS. This intervention was applied to a group of obese women and evaluated through a qualitative full-cycle survey. The results indicate that the GPSS provides important tools for emotional self-regulation and favors participants' autonomy and control over their food choices.